The Impact of Green Banking on Profitability (Study on Banking Sector Listed on Indonesia Stock Exchange (IDX) Period 2016-2022) - Chen Tia; Hasnawati, Sri; Faisol, Ahmad (International Journal of Asian Business and Management, 2023)
The objective of this study is to determine the impact of green banking on profitability of banks in Indonesia. The sample of this research is the Indonesian banking sector during the period 2016 to 2022. The data utilized in this study were obtained from secondary sources, specifically from 9 banks. In total, there were 63 observations. The measurement of profitability ratio is conducted through the utilization of Return on Asset (ROA). The study using data panel analysis resulting green banking using 21 reported items of Green Banking Disclosure Index positively have impact on profitability of banks. It implies that the increasing green banking practices will increase the profitability of banks, highlighting the use of the separate green banking index measurements outside of the total green banking index might be considered by future researchers